Epistemological Study of Ḥasan Baṣrī's Qirā'ah: Methodology and its Implications in Qur'anic Interpretation - Al Farabi, Fahmi Akhyar; Khalil Kanzu, Muhammad; Rohman, Abdur; Aziz, Ienash Huwaida (JOURNAL OF QUR'AN AND HADITH STUDIES, 2024)
The science of qirā’at is one of the important elements in reciting the Al-Qur'an. The author takes one of the lines of qirā'at narrators, namely Ḥasan Baṣrī, a famous qirā'at imam. This research uses a descriptive analysis method with data processing using the library method. The result of this research is an explanation of the meaning of qirā'ah syāżah which does not fulfill the pillars of qirā'ah mutawātir. The qirā'ah syāżah attributed to Ḥasan Baṣrī with several examples does not show much change in meaning in the interpretation of the Qur'an, but the differences in reading are caused by the specificity of each tribe or region which cannot pronounce certain letters or words. So, Qirā'at ṣāḍḍah Ḥasan Baṣrī is a reading of the Qur’an that should not be practiced as daily reading. This Qirā’at can only be studied to ensure that this knowledge does not get swallowed up by time.